2018
DOI: 10.3390/rs10060942
|View full text |Cite
|
Sign up to set email alerts
|

Potential of Different Optical and SAR Data in Forest and Land Cover Classification to Support REDD+ MRV

Abstract: The applicability of optical and synthetic aperture radar (SAR) data for land cover classification to support REDD+ (Reducing Emissions from Deforestation and Forest Degradation) MRV (measuring, reporting and verification) services was tested on a tropical to sub-tropical test site. The 100 km by 100 km test site was situated in the State of Chiapas in Mexico. Land cover classifications were computed using RapidEye and Landsat TM optical satellite images and ALOS PALSAR L-band and Envisat ASAR C-band images. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 37 publications
(60 reference statements)
0
18
2
Order By: Relevance
“…There are a number of recent studies that argue in support of a combined use of SAR and optical data for tropical forest monitoring [3,[50][51][52][53]. Recent results indicate that a combined use can improve tropical forest monitoring for burnt area detection [14], for forest/non-forest mapping [52,54,55], for biomass assessment [56][57][58], and for deforestation and degradation monitoring [45,51,59]. A combination of ALOS PALSAR data and Landsat data was also used to enhance the discrimination of mature forest, secondary forest, and non-forest areas [60].…”
Section: Forest Disturbance Monitoring Combining Sar and Optical Datamentioning
confidence: 99%
“…There are a number of recent studies that argue in support of a combined use of SAR and optical data for tropical forest monitoring [3,[50][51][52][53]. Recent results indicate that a combined use can improve tropical forest monitoring for burnt area detection [14], for forest/non-forest mapping [52,54,55], for biomass assessment [56][57][58], and for deforestation and degradation monitoring [45,51,59]. A combination of ALOS PALSAR data and Landsat data was also used to enhance the discrimination of mature forest, secondary forest, and non-forest areas [60].…”
Section: Forest Disturbance Monitoring Combining Sar and Optical Datamentioning
confidence: 99%
“…The RF disturbance probability model of Sentinel-1 had a low PA of disturbance (58.6%), indicating large omission errors of disturbance. This result was not surprising because C-band SAR is generally less sensitive to forest structures [42,43]. Although we applied careful preprocessing to remove noise from the SAR backscatter coefficients, such as terrain correction, the mountainous regions in the study area might have affected the accuracy of detection, because rugged terrain affects the geometric and radiometric conditions of SAR observations.…”
Section: Discussionmentioning
confidence: 95%
“…Sentinel-1 data have been used for crop mapping [36,37], land cover classification [38][39][40] and forest monitoring [41]. Although shorter wavelength (C-band) SAR data is usually unsuitable for estimating forest structures [42,43], several studies have reported encouraging results using Sentinel-1 time series data for detecting disturbances and mapping deforestation in tropical regions [34,44].…”
Section: Introductionmentioning
confidence: 99%
“…As reference data set, three Pléiades images, two from 19 and one from 21 November 2016 (© Centre National D'Etudes Spatiales (CNES)/AirbusDS) in 50 cm resolution and a SPOT-5 scene (©CNES) dated 25 June 2015 in 5 m resolution from the SPOT5-Take5 program were made available through ESA and the Centre National D'Etudes Spatiales (CNES) (Figure 9). We follow the approach of [47] based on a systematic sampling grid. As we have trained the MLC with in situ knowledge, RapidEye imagery from 2013, and GoogleEarth, the SPOT5 and Pléiades VHR data are independent and solely used for validation.…”
Section: Validation and Inter-comparison Approachmentioning
confidence: 99%